Memahami Tugas Kekhalifahan sebagai Amanat Mengembangkan IPTEK dan Pemberdayaan Manusia - Siti Sarifah; Yurna Bachtiar; Dwi Suryani Kurniawan; Jenal nurhakim; saeful bahri alamsyah putra (Universitas Palangka Raya, 2026)
The mandate of khilafah establishes a foundational moral responsibility for human beings in developing science and technology (IPTEK). This study aims to analyze the concept of the khilafah mandate as an ethical foundation for technological advancement, methods to align technology with environmental and human values, and its utilization for human empowerment. Using a qualitative approach with a literature review (secondary data analysis), this research examines various academic journals, reference books, and Islamic classical texts. The findings indicate that human responsibility as Allah's vicegerent (khalifah) demands that intellectual capacity and scientific development be guided by theological values rather than personal desires (hawa nafsu). Aligning technological progress with nature requires an understanding of Qur'anic signs regarding cosmological balance.